2023
DOI: 10.1021/acs.energyfuels.3c03411
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification Effect on V-Doped Ti3C2Tx as Bifunctional Catalyst Electrodes for Symmetric Supercapacitor and the Hydrogen Evolution Reaction

Jagadeesh Ramadoss,
Arumugam Sonachalam,
Mani Govindasamy

Abstract: MXene-based composite materials have plenty of characteristics, such as high surface area, excellent metallic conductivity, rapid oxidation, and reduction activity. These materials have many advantages for use in modified electrodes for energy storage and conversion applications. However, their applicability in several types of industries has been significantly limited as a result of issues with surface aggregation and oxidation. In this study, we improved the electrochemical properties of the electrodes by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…This feature aligns with the growing demand for energy storage systems that not only deliver high performance but also exhibit longevity and resilience [4,5]. The enduring ability of metal oxides, particularly in composite or spinel configurations, to retain charge significantly contributes to the advancement of supercapacitors capable of meeting the demands across various applications [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 76%
“…This feature aligns with the growing demand for energy storage systems that not only deliver high performance but also exhibit longevity and resilience [4,5]. The enduring ability of metal oxides, particularly in composite or spinel configurations, to retain charge significantly contributes to the advancement of supercapacitors capable of meeting the demands across various applications [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 76%
“…The capacitance values are shown in Figure h . In another work, Ramadoss et al observed the improvement in the charge storage behavior of the MXene after V-doping on the layered K + -Ti 3 C 2 T x , which is shown in Figure i . Fatima et al incorporated Nb atoms into the MXene in order to improve its ionic conductivity and stability.…”
Section: Doped Mxene In Supercapacitorsmentioning
confidence: 97%
“…(i) CV and GCD curves of various V-doped K + -Ti 3 C 2 T x . Reprinted with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Doped Mxene In Supercapacitorsmentioning
confidence: 99%